Effects of prolonged aerobic exercise and training intensity on memory cognition. - Xinnan Li; Junwei Qian; Jiajin Tong; Zhonghui He (PLoS ONE)
This study aims to explore whether the impact of varying aerobic exercise intensities on knowledge acquisition is influenced by exercise intensity and gender. The results lay the groundwork for selecting suitable aerobic exercise intervention programs, considering exercise intensity and gender, to enhance knowledge acquisition. Employing a mixed-design approach, a sample of 569 college students engaged in 8 weeks of aerobic exercise sessions with moderate and low intensity, incorporating basketball and badminton. Knowledge acquisition effects were assessed using questionnaires targeting distinct knowledge levels. Declarative and procedural knowledge levels across different acquisition types were evaluated pre and post-exercise intervention for the low-intensity, moderate-intensity, and control groups. The findings reveal that both moderate and low-intensity aerobic exercises distinctly and positively impact college students' knowledge levels, with no discernible gender-related alterations.